Manufacturing technology acquisition - Mallon, Michael John (Cranfield University, 2002)
This thesis concerns the acquisition of newly developed production equipment in factories. Types of Manufacturing Technology Acquisition (MTA) can range from in-house development through to outright purchase from a supplier. MTA projects often fail because the new equipment fails to perform well enough or the expected financial benefits are not achieved. The purpose of this research has been to find out how to select the right manufacturing technology acquisition projects, and having chosen them, how to make them successful. Very little guidance on this subject was found in the literature. Therefore the approach taken was to adapt techniques widely used in the much more deeply researched field of New Product Development (NPD). The Success Factor method was applied by conducting interviews with managers in a number of factories to develop lists of factors thought to affect success or failure in their MTA projects. The Portfolio method from NPD was adapted to the case of managing a total MT`A budget, and developed through its use in three annual cycles of equipment acquisition in the researcher's Company. A formula for Expected Commercial Value in NPD was modified to become Expected Manufacturing Benefit, and tried out in practice. An important consideration in manufacturing equipment projects was discovered to be the replication of projects which had proved successful, and ways to incorporate this factor into the project selection procedure were developed. A detailed case study of a single project was carried out, which verified the validity of the findings at the level of a single project. This case study also revealed the considerable impact that corporate strategic events can have on technology acquisitions. This led to a case study on corporate strategy in the Company being carried out. Finally the findings were brought together to present a complete model for managing MTA.